Study on Feeding Diversification in Infants Aged 6 to 24 Months at the Therapeutic Nutrition Unit in the Paediatric Department of the Regional Hospital Center (RHC) of Man (Côte d’Ivoire) - Daouda, Nimaga; Chantal, Soro Lêniféré; Armand, Kouadio Kouakou Kouassi; Awa, Diarrassouba; Nestor, Kouassi Kouakou; Louise, Anin-Atchibri Anin (Current Nutrition & Food Science, 2025)
IntroductionInappropriate infant feeding practices are a factor in malnutrition in western Côte d'Ivoire, which can cause several problems. In fact, in this part of the country, 26% of children under the age of 5 are undernourished, and 6% of these children are wasted. In order to assess knowledge and practices regarding infant feeding, this survey was carried out among mother-child pairs at the Regional Hospital Center (RHC) of Man.MethodsThis was a descriptive survey carried out from February to March 2023 in the therapeutic nutrition unit of the paediatric department of the RHC of Man. The target population consisted of 250 mother-child pairs attending the unit. The questions mainly focused on the sociodemographic characteristics of the infants, the socio-economic characteristics of the household, supplementary feeding, and information channels related to nutrition and feeding of children aged between 6 and 24 months.ResultsThe age group of 12 to 18 months was the most representative (40%), with a female predominance (56%). Exclusive breastfeeding was practiced in only 42% of infants, with early introduction of water in 63.6% between 4 and 6 months. A total of 98.8% of infants were up to date with their vaccination schedules, and 36.4% received medical follow-up. Diversification began before 6 months in 62% of infants, and in the majority of cases, cereal-based porridge was introduced between 4 and 6 months. The introduction of vegetables and meat was delayed, occurring between 7 and 12 months (42.4%) and between 13 and 18 months (28%) respectively. Breastfeeding cessation occurred in 23.6% between 13 and 18 months. The most common difficulties in supplementary feeding were childhood illness (38%) and children's refusal to eat (26%).ConclusionInadequate practices and introduction of complementary foods were noted in the majority of cases. Hence, there is an urgent need to educate mothers on WHO recommendations regarding infant feeding diversification.
Keywords: practices